Ulcerative Colitis as a Novel Cause of Increased Need for Levothyroxine - Virili, Camilla; Stramazzo, Ilaria; Santaguida, Maria Giulia; Bruno, Giovanni; Brusca, Nunzia; Capriello, Silvia; Cellini, Miriam; Severi, Carola; Gargano, Lucilla; Centanni, Marco (Frontiers in Endocrinology, 2019)
Background: Thyroxine absorption takes place at the small intestine level and several disorders affecting this intestinal tract lead to thyroxine malabsorption. An increased need for thyroxine has also been observed in gastric disorders due to variations in drug dissolution and/or in its ionization status. Ulcerative colitis (UC) is an inflammatory bowel disease that has been postulated as a potential cause of the increased need for thyroxine, but there is a lack of evidence on this topic. This study is aimed at measuring the thyroxine requirement in hypothyroid patients with UC. Patients and Methods: Among 8,573 patients with thyroid disorders consecutively seen in our referral center from 2010 to 2017, we identified 34 patients with a definite diagnosis of UC. Thirteen of them were hypothyroid (12 F/1 M; median age = 53 years), bearing UC during the remission phase and in need for thyroxine treatment, thus representing the study group. The dose of T4 required by UC patients has been compared to the one observed in 51 similarly treated age- and weight-matched patients, compliant with treatment and clearly devoid of any gastrointestinal and /or pharmacological interference. Results: To reach the target serum TSH, the dose of thyroxine had to be increased in twelve out of thirteen (92%) hypothyroid patients with ulcerative colitis. The median thyroxine dose required by UC patients was 1.54 μg/kg weight/day, that is 26% higher than the control patients, to reach a similar TSH (1.23 μg/kg weight/day; p = 0.0002). Since half of our study group consisted of patients aged over 60 years old, we analyzed the effect of age on the subdivision in two classes. Six out of seven (86%) adult patients (<60 years) required more T4 than those in the respective control group (1.61 vs. 1.27 μg/kg weight/day; +27%; p < 0.0001). An increased dose (+17%; p = 0.0026) but to a lesser extent, was also observed in all patients over 60 years, as compared to the control group. Conclusions: In almost all hypothyroid patients with UC, the therapeutic dose of thyroxine is increased. Therefore, ulcerative colitis, even during clinical remission, should be included among the gastrointestinal causes of an increased need for oral thyroxine.